Bioaccumulation of therapeutic drugs by human gut bacteria - Klünemann, Martina; Andrejev, Sergej; Blasche, Sonja; Mateus, Andre; Phapale, Prasad; Devendran, Saravanan; Vappiani, Johanna; Simon, Bernd; Scott, Timothy A.; Kafkia, Eleni; Konstantinidis, Dimitrios; Zirngibl, Katharina; et al. (Nature (London), 2021)
Bacteria in the gut can modulate the availability and efficacy of therapeutic drugs. However, the systematic mapping of the interactions between drugs and bacteria has only started recently 1 and the main underlying mechanism proposed is the chemical transformation of drugs by microorganisms (biotransformation). Here we investigated the depletion of 15 structurally diverse drugs by 25 representative strains of gut bacteria. This revealed 70 bacteria–drug interactions, 29 of which had not to our knowledge been reported before. Over half of the new interactions can be ascribed to bioaccumulation; that is, bacteria storing the drug intracellularly without chemically modifying it, and in most cases without the growth of the bacteria being affected. As a case in point, we studied the molecular basis of bioaccumulation of the widely used antidepressant duloxetine by using click chemistry, thermal proteome profiling and metabolomics. We find that duloxetine binds to several metabolic enzymes and changes the metabolite secretion of the respective bacteria. When tested in a defined microbial community of accumulators and non-accumulators, duloxetine markedly altered the composition of the community through metabolic cross-feeding. We further validated our findings in an animal model, showing that bioaccumulating bacteria attenuate the behavioural response of Caenorhabditis elegans to duloxetine. Together, our results show that bioaccumulation by gut bacteria may be a common mechanism that alters drug availability and bacterial metabolism, with implications for microbiota composition, pharmacokinetics, side effects and drug responses, probably in an individual manner. An analysis of the interactions between 15 drugs and 25 gut bacterial strains shows that bioaccumulation of drugs within bacterial cells is another mechanism through which gut microorganisms can alter drug availability and efficacy.